Efecto del uso de agroquímicos en el agua y la salud humana en comunidades cercanas a la bananera la Julia del Cantón Babahoyo. Año 2016 - Aguilar Montiel, Ernesto Lizardo (2016)
The research "Effect of agrochemicals on water and its impact on the quality of life of communities near the banana La Julia in Babahoyo canton. Year 2016, "had as general objective to evaluate contents of organophosphates and organochlorines present in the liquid vital for human consumption due to the constant fumigation in the banana plantations of the La Julia farm. It was determined that the presence of organophosphates does not exceed the maximum permissible value 0.1 mg / liter, and the result of the water sample is 0.01508 mg / liter therefore the surface water of the locality does not present any negative observation of This parameter. In the evaluation of the toxicity of the current consumption water of the nearby communities, which was determined by the quantity of organochlorines (mg / liter), it was determined that this parameter does exceed the maximum permissible value 0,01 mg / liter, where the result of the Sample of water is 0.018 mg / liter therefore the surface water of the locality is not suitable for human consumption. In the determination of the percentage of symptoms of diseases to the people by the effect of the fumigation by means of a survey to the inhabitants of communities near to the farm the Julia it is observed that among the most common symptoms: headache 22%, lacrimation 17% Red eyes 11%, as the most important. The water consumed by the inhabitants of the communities 36% is potable and 55% of wells. 74% do use protective equipment. In the Quality of life was determined that 41% has primary and 45% no academic level; The majority only access electric light (96%); 100% access roads are ballast; Social security 30% access to general insurance and 50% to peasant insurance. Weighted all the study factors gives a report of 61,33 over 100 points, so it is concluded that the index of quality of life of people is low around the area of influence of the farm Julia as it corresponds to the interval of 60 - 69 points.